Credibility Effects of Price Controls in Disinflation Programs - Agenor, Pierre-Richard (IMF Working Papers; Working Paper ;, 1992)
This paper examines whether price controls may enhance the credibility of a disinflation program, using a framework in which agents behave strategically. The analysis indicates that a partial price freeze is not fully credible, and may result in inflation inertia. The authorities may be able to determine optimally the intensity of price controls so as to minimize the policy loss associated with a discretionary monetary strategy. But the optimal intensity of controls is shown to be significantly different from zero only if the cost of enforcing price ceilings is not too high, or if the weight attached to price distortions in the policymaker's loss function is small.